Oculo-respiratory Syndrome: A New Influenza Vaccine-Associated Adverse Event? - Skowronski, Danuta M.; Strauss, Barbara; De Serres, Gaston; MacDonald, Diane; Marion, Stephen A.; Naus, Monika; Patrick, David M.; Kendall, Perry (Clinical infectious diseases, 2003)
During the 2000–2001 influenza immunization campaign in Canada, a new adverse event, oculo-respiratory syndrome (ORS), was noted in association with administration of vaccine supplied by one manufacturer. The original case definition for ORS specified bilateral conjunctivitis, facial edema, or respiratory symptoms beginning 2–24 h after influenza vaccination and resolving within 48 h after onset. To characterize the spectrum, severity, and impact of ORS, we contacted persons who had reported any influenza vaccine-associated adverse event in British Columbia, Canada, during the 2000–2001 vaccination campaign. With use of a standardized telephone interview, we collected information from 609 (79%) of 769 eligible persons. Thirteen percent of ORS-affected persons reported onset ⩽2 h after vaccination, 27% experienced symptoms for >48 h, and 42% considered the symptoms to be severe. The surveillance case definition for ORS for 2001–2002 was revised to include onset ⩽24 h after vaccination, with no restriction on duration. ORS should be incorporated into annual influenza vaccine safety monitoring.